2022-RA-619-ESGO Less is more? Simple hysterectomy versus radical hysterectomy in FIGO 2018 stage IA2 cervical carcinoma: a pan-birmingham gynaecological cancer centre population-based longitudinal cohort study. (20th October 2022) - Audrey Kwong, Fong Lien; Tranoulis, Anastasios; Yap, Jason; Elattar, Ahmed; Singh, Kavita; Balega, Janos
Abstract : Introduction/Background: To compare post-operative morbidity and long-term survival outcomes of simple hysterectomy (SH) versus radical hysterectomy (RH) in FIGO 2018 stage IA2 cervical cancer (CC). Methodology: Using the Pan-Birmingham Gynaecological Cancer Centre database, we identified women with stage IA2 CC between 2008 and 2020. Clinicopathological and treatment data were collated, and progression-free (PFS) and overall survival (OS) analysed via the Kaplan-Meier method, Log-rank test and Cox regression. Post-operative complications were assessed via the Clavien-Dindo classification. Results: Of the 46 women enrolled, 28 (60.7%) underwent SH and 18 (29.3%) RH. There was no significant difference in age, BMI, parity or ethnicity between the two groups. For SH vs RH, 78.6% vs 38.9% ( p-value =0.01 had disease of squamous histology, 96.4% vs 94.4% ( p-value =0.74) underwent large loop excision of the transformation zone prior to surgery, 7.14% vs 44.4% ( p-value =0.003) had grade 3 disease, 71.4% vs 77.8% ( p-value =0.22) underwent pelvic lymphadenectomy, and 3.8% vs 5.6% ( p-value =0.12) had severe (CD>3) post-operative complications. Women with adenocarcinoma or adenosquamous carcinoma (OR=1.6, p-value =0.01) or grade 3 disease (OR=21.02, p-value =0.0004) were more likely to undergo RH. One recurrence was observed in each group. The mean PFS in SH vs RH group was 139.44 vs 159.00 months. SH was not associated with shorter PFS in either univariate (HR=0.59, p-value =0.72) or multivariate analysis (aHR=0.24, p-value =0.36). One death was observed in the RH group. The mean OS in SH vs RH group was 139.44 vs 153.85 months ( p-value =0.51). Conclusion: SH does not smilingly associated with poorer oncological outcomes in stage IA2 CC. This evidence is in line with previous observational studies. The results of randomised SHAPE trial are being awaited to draw firmer conclusions.